Tuberosity reconstruction baseplate for shoulder hemiarthroplasty: Morphological design and biomaterial application - Ding, Zhentao; Ju, Jiabao; Ma, Mingtai; Zhang, Yichong; Chen, Jianhai (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Shoulder hemiarthroplasty is commonly performed for complex proximal humeral fractures. However, hemiarthroplasty is prone to tuberosity malposition and migration, resulting in a low rate of tuberosity healing. We proposed to design a tuberosity reconstruction baseplate to assist in tuberosity integration and to evaluate the mechanical properties of baseplate made from the novel biomaterial carbon fiber reinforced polymer (CFRP) composites. Methods: The three-dimensional model of native proximal humerus was constructed by computed tomography (CT) data. The morphological design of baseplate was based on the tuberosity contour and rotator cuff footprint. Finite element models were created for different thicknesses of CFRP composites, poly (ether-ether-ketone) (PEEK) and titanium-nickel (TiNi) alloy. The permissible load and suture hole displacements were applied to evaluate the mechanical properties. Results: The structurally optimized model made of CFRP composites provided superior strength and deformability, compared to the PEEK material and TiNi alloy. Its permissible load was above 200 N and the suture hole displacement was between 0.9 and 1.4 mm. Conclusions: This study proposed a method for designing tuberosity reconstruction baseplate based on morphological data and extended the application of biomaterial CFRP composites in orthopedics field. The optimized model made of CFRP composites allowed a certain extent of elastic deformation and showed the possibility for dynamic compression of tuberosity bone blocks.